2015
DOI: 10.1016/j.econedurev.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Does computer-assisted learning improve learning outcomes? Evidence from a randomized experiment in migrant schools in Beijing

Abstract: a b s t r a c tThe education of the disadvantaged population has been a long-standing challenge to education systems in both developed and developing countries. Although computer-assisted learning (CAL) has been considered one alternative to improve learning outcomes in a costeffective way, the empirical evidence of its impacts on improving learning outcomes is mixed. This paper uses a randomized field experiment to explore the effects of CAL on student academic and non-academic outcomes for students in migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 20 publications
3
82
2
Order By: Relevance
“…In a number of contexts, including China (Lai et al 2011;Lai et al 2013;Yang et al 2013;Mo et al 2014), Chile (Imbrogno 2014), Ecuador (Carillo, Onofa & Ponce 2010), India (Banerjee et al 2008;Linden 2008) and Mexico (Imbrogno 2014), computer-assisted learning programmes have improved maths test scores quite substantially. The programmes where computer-assisted learning improved outcomes share a number of characteristics.…”
Section: What Have We Learned?mentioning
confidence: 99%
“…In a number of contexts, including China (Lai et al 2011;Lai et al 2013;Yang et al 2013;Mo et al 2014), Chile (Imbrogno 2014), Ecuador (Carillo, Onofa & Ponce 2010), India (Banerjee et al 2008;Linden 2008) and Mexico (Imbrogno 2014), computer-assisted learning programmes have improved maths test scores quite substantially. The programmes where computer-assisted learning improved outcomes share a number of characteristics.…”
Section: What Have We Learned?mentioning
confidence: 99%
“…Integrating Information and Communication Technology (ICT) into the classroom is a promising approach to help disadvantaged students across the world (Bakar, Inal, & Cagiltay, 2006;Ebner & Holzinger, 2007;Pal, Pawar, Brewer, & Toyama, 2006;Banerjee, Cole, Duflo, & Linden, 2007;Lai, Luo, Zhang, Huang, & Rozelle, 2011;Mo, Zhang, Luo, et al, 2014). Policymakers in developed and developing countries have tested various methods to use ICT for innovation and improvement of poor performance students (Sweet & Meates, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in both developed and developing countries have shown inconsistent evidence of the educational benefits of using ICT in schools (e.g. Banerjee et al, 2007;Barrow, Markman, & Rouse, 2008;Almekhlafi, 2006;Olibie, 2010;Lai et al, 2012Lai et al, , 2013Angrist & Lavy, 2002;Rouse & Krueger, 2004;Hlas & Vuksanovich, 2007;Dynarshki et al, 2007;Chien, 2011). For example, Banerjee et al (2007) showed that a Computer Assisted Learning (CAL) programme significantly helped students increase math scores.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers consider influence of the computer on pupils' behavior when training them by means of game technologies [8,9], for estimation of knowledge [10][11][12][13], as an assistant for development of discipline on remote access, for exchange of knowledge on social networks [14,15], when training mentally retarded pupils, students with the low level of knowledge [16,17], etc.…”
Section: Introductionmentioning
confidence: 99%